Characteristics of natural rubber/latex compound waste (NR/LCW) blends in the perspective of shoe soles application - Ihda Novia Indrajati; Ike Setyorini; Indah Kumalasari (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2019)
Being difficult to degrade, latex compound waste (LCW) should be handled carefully. In this study the possibility of application of LCW for shoe sole was evaluated. LCW was derived from latex-based industry from local factory. It was blended with natural rubber (NR) with the ratio ranging from 100/0; 90/10; 80/20; 70/30; 60/40 and 50/50. Cure characteristics and mechanical properties including tensile strength, elongation at break, hardness and tear strength, were measured before and after aging. Abrasion loss and slip resistance were also taken account. The results finding showed that crosslink density of the NR/LCW blends were higher than of control. Mechanical properties of the blends were greatly affected by crosslink density. Compared to control, the NR/LCW blends provided lower tensile and elongation, but higher in tear strength, hardness and abrasion loss. Heat aging tended to decrease the mechanical properties. LCW improved the coefficient of friction (CoF).